2021
DOI: 10.3390/curroncol28040277
|View full text |Cite
|
Sign up to set email alerts
|

What Matters in Cancer Survivorship Research? A Suite of Stakeholder-Relevant Outcomes

Abstract: The outcomes assessed in cancer survivorship research do not always match the outcomes that survivors and health system stakeholders identify as most important in the post-treatment follow-up period. This study sought to identify stakeholder-relevant outcomes pertinent to post-treatment follow-up care interventions. We conducted a descriptive qualitative study using semi-structured telephone interviews with stakeholders (survivors, family/friend caregivers, oncology providers, primary care providers, and cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The cancer types represented by survivors and family/friend caregivers were breast, colorectal, genitourinary, ovarian, melanoma, and hematologic, and more than half of these participants were between the ages of 40–64 (55.6%). More details on participant demographics can be found in [ 17 ]. Stakeholder-relevant interventions related to survivors’ psychosocial needs were classified into the following five intervention categories: information provision, peer support, navigation, knowledge translation interventions, and caregiver-specific supports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cancer types represented by survivors and family/friend caregivers were breast, colorectal, genitourinary, ovarian, melanoma, and hematologic, and more than half of these participants were between the ages of 40–64 (55.6%). More details on participant demographics can be found in [ 17 ]. Stakeholder-relevant interventions related to survivors’ psychosocial needs were classified into the following five intervention categories: information provision, peer support, navigation, knowledge translation interventions, and caregiver-specific supports.…”
Section: Resultsmentioning
confidence: 99%
“…The data for this paper are part of a larger dataset collected for a prior study [ 17 ]. Data were collected via one-on-one, semi-structured telephone interviews between the research associate and participant.…”
Section: Methodsmentioning
confidence: 99%
“…17 Stakeholders in this study reported that the outcome of returning to life after cancer treatment/adjusting to a "new normal" was of priority importance. 17 Similarly, in their study, Kain et al identified returning to "normal" as a major theme of importance in a group of sarcoma survivors. 18 Ore and Foli published a concept analysis on reintegration post-cancer treatment.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, other studies have found that outcomes important to patients and other stakeholders are overlooked or considered unimportant by researchers 15,16 . A descriptive qualitative study with health care providers, administrators, survivors, and caregivers from across Canada was conducted to identify stakeholder-relevant outcomes pertinent to follow-up care interventions 17 . Stakeholders in this study reported that the outcome of returning to life after cancer treatment/adjusting to a “new normal” was of priority importance 17 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation